Physicochemical characteristics of forest soils in Tarai and Siwalik regions of Nepal - Sapkota, Ramesh P.; Stahl, Peter D.; Rijal, Kedar (Nepal Journal of Environmental Science, 2017)
Soils are important components of every terrestrial ecosystem. In Nepal, terrestrial ecosystems of Tarai and Siwalik regions are highly vulnerable due to intense anthropogenic disturbances. Forest depletion and land degradation have posed substantial impacts on soil quality. This review paper focuses on identifying the status of physical and chemical characteristics of forest soils in Tarai and Siwalik regions. For the purpose, published articles from various sources, as well as publications of Government of Nepal were reviewed. The study showed variation in physicochemical characteristics of soils in different regions. The land areas covered with vegetation were found effective in controlling erosion and consequently retention of important chemical properties of soils. The scientific studies on soil physical, chemical and biological quality seem inadequate. Standard research framework and sampling designs are required in future studies, so that comparisons on soil properties across different degraded and/or other land-use categories can be made. There is need of development of scientific database on soil quality for supporting future ecosystem management and restoration programs.